2003
DOI: 10.1530/eje.0.1490425
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal course of persistently short children born small for gestational age (SGA) compared with idiopathic short children born appropriate for gestational age (AGA)

Abstract: Objective: Few data are available on the pubertal development of children born small for gestational age (SGA) who fail to show catch-up growth. Design: A longitudinal analysis compared the pubertal course of persistently short children born SGA compared to children with idiopathic short stature who were appropriate for gestational age (AGA). One hundred and twenty-eight short children (height SDS , 21.7), including 76 (31 boys) born SGA and 52 (22 boys) born AGA, were regularly followed from early childhood t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 31 publications
(19 reference statements)
3
64
0
9
Order By: Relevance
“…Growth analyses of TPG from Lazar et al [39] and Vicens-Calvet et al [40] suggest that TPG in SGA is normal for age at puberty onset and sex. During long-term GH therapy TPG was documented in the studies of Rosilio et al [41] and Boonstra et al [42].…”
Section: Discussionmentioning
confidence: 99%
“…Growth analyses of TPG from Lazar et al [39] and Vicens-Calvet et al [40] suggest that TPG in SGA is normal for age at puberty onset and sex. During long-term GH therapy TPG was documented in the studies of Rosilio et al [41] and Boonstra et al [42].…”
Section: Discussionmentioning
confidence: 99%
“…52 The relationship of body fat and puberty timing is reviewed by Kaplowitz. 53 Some studies found that children who had a low birth weight (defined as Ͻ2500 g) or were small for gestational age (typically defined as birth weight Ͻ10th percentile for gestational age and gender) are more likely to have advanced timing of puberty (girls and boys 54 ; girls only 55 ); however, other results are mixed. For example, 1 study found an association between small size at birth and early puberty in girls but not boys, 56 and another found no differences between pubertal timing in children who were born at very low birth weight (Ͻ1251 g) and control subjects of both genders.…”
Section: Issues In Secular Trend Analysis For Pubertal Timing Studiesmentioning
confidence: 99%
“…The change in the timing of onset of puberty appears to show a gender dimorphism, in that girls, but not boys, start puberty a few months earlier than normal if born SGA [56] and progress more quickly through puberty [7, 57, 58]. Another study, however, found that pubertal onset was in the early-normal range for gender, growth pattern during the pubertal spurt was different, but total pubertal height gain was comparable [59]. Overall, changes in pubertal maturation due to low birth weight do not appear to be profound [60].…”
Section: Male Reproductive Hormones and Pubertymentioning
confidence: 99%